Antioxidant Activities and Cytotoxicity of the Regulated Calcium Oxalate Crystals on HK-2 Cells of Polysaccharides from Gracilaria lemaneiformis with Different Molecular Weights - Jing-Hong Liu; Yu-Yun Zheng; Jian-Ming Ouyang (Foods, 2023)
The antioxidant activities of seven degraded products (GLPs) with different molecular weights (Mw) of polysaccharides from Gracilaria lemaneiformis were compared. The Mw of GLP1–GLP7 were 106, 49.6, 10.5, 6.14, 5.06, 3.71 and 2.42 kDa, respectively. The results show that GLP2 with Mw = 49.6 kDa had the strongest scavenging capacity for hydroxyl radical, DPPH radical, ABTS radical and reducing power. When Mw < 49.6 kDa, the antioxidant activity of GLPs increased with the increase in Mw, but when Mw increased to 106 kDa, their antioxidant activity decreased. However, the ability of GLPs to chelate Fe2+ ions increased with the decrease in polysaccharide Mw, which was attributed to the fact that the polysaccharide active groups (–OSO3– and –COOH) were easier to expose, and the steric hindrance was smaller when GLPs chelated with Fe2+. The effects of GLP1, GLP3, GLP5 and GLP7 on the crystal growth of calcium oxalate (CaOx) were studied using XRD, FT-IR, Zeta potential and thermogravimetric analysis. Four kinds of GLPs could inhibit the growth of calcium oxalate monohydrate (COM) and induce the formation of calcium oxalate dihydrate (COD) in varying degrees. With the decrease in Mw of GLPs, the percentage of COD increased. GLPs increased the absolute value of the Zeta potential on the crystal surface and reduced the aggregation between crystals. Cell experiments showed that the toxicity of CaOx crystal regulated by GLPs to HK-2 cells was reduced, and the cytotoxicity of CaOx crystal regulated by GLP7 with the smallest Mw was the smallest, which was consistent with the highest SOD activity, the lowest ROS and MDA levels, the lowest OPN expression level and the lowest cell necrosis rate. These results suggest that GLPs, especially GLP7, may be a potential drug for the prevention and treatment of kidney stones.